Rancang Bangun Prototipe Sistem Multilateration 2-Dimensi Menggunakan Data ADS-B - I Made Astawa; Siswayudi Azhari; I Putu Ananta Yogiswara; Widrianto Sih Pinastiko (Ultima Computing : Jurnal Sistem Komputer, 2019)
Multilateration (MLAT) is a technology used to determine the position of an object by using a Time Difference of Arrival (TDOA). MLAT is used at airports as one of the sensors in the A-SMGCS system to determine the position of an aircraft or vehicle. Developing an MLAT system should ideally be done at the airport because it requires aircraft and vehicle objects that are already equipped with ADS-B transmitters, but developing an MLAT system at the airport requires high costs for equipment installation and licensing because it risks disrupting airport operations and can disrupt existing systems . The Center of Technology for Electronics - BPPT is developing the A-SMGCS system and is based in the serpong puspiptek area, where this area has a large enough area, making it possible to design prototypes of the MLAT system. Three ADS-B receivers are placed in three different buildings that are still connected to a computer network, so that data collection from each receiver can be done through the BPPT local network. The object to be calculated is using a car equipped with an ADS-B transmitter. To get more accurate results, every time the receiver is synchronized using GPS. The experimental results show that there is a difference between the position data sent by the ADS-B transmitter and the results of the MLAT calculation, this is due to the difference in height of the three receivers, accuracy of GPS and accuracy of the ADS-B receiver timestamp used. Although there are differences, the proof of concept design of this system is in accordance with the characteristics of the MLAT system. The benefit gained from the design of this prototype is that it can develop an MLAT system in a place that is not high risk with low cost but the results can be applied at the airport.